Cardiac findings in infants with in utero exposure to Zika virus- a cross sectional study. - Dulce H G Orofino; Sonia R L Passos; Raquel V C de Oliveira; Carla Verona B Farias; Maria de Fatima M P Leite; Sheila M Pone; Marcos V da S Pone; Helena A R Teixeira Mendes; Maria Elizabeth L Moreira; Karin Nielsen-Saines (Public Library of Science (PLoS), 2018)
Antenatal exposure to Zika virus (ZIKV) is related to severe neurological manifestations. A previous study in Brazil reported an increased incidence of non-severe congenital heart defects in infants with diagnosis of congenital Zika syndrome but without laboratory confirmation of ZIKV infection in the mother or infant. The objective of this study is to report echocardiographic (ECHO) findings in infants with laboratory confirmed antenatal exposure to ZIKV.Cross sectional study of cardiologic assessments of infants born between November 2015 and January 2017 with confirmed vertical exposure to ZIKV in Rio de Janeiro, Brazil.The study enrolled 120 children with a median age of 97 days (1 to 376 days). In utero exposure to ZIKV was confirmed in 97 children (80,8%) through positive maternal polymerase chain reaction (PCR) results during pregnancy or a positive PCR result at birth; 23 additional children (19.2%) had maternal positive PCR results during pregnancy and postnatally. Forty- eight infants (40%) had cardiac defects noted on ECHO. Thirteen infants (10.8%) had major cardiac defects (atrial septal defect, ventricular septal defect, patent ductus arteriosus). None of the defects were severe. The frequency of major defects was higher in infants whose mothers had a rash in the 2nd trimester of pregnancy, or who had altered Central Nervous System (CNS) imaging postnatally or were preterm.Infants with in utero ZIKV exposure have a higher prevalence of major cardiac defects, however none were severe enough to require immediate intervention. For this reason, guidelines for performance of postnatal ECHO in this population should follow general newborn screening guidelines, which significantly reduces the burden of performing emergent fetal or neonatal ECHOs in a setting where resources are not available, such as most Brazilian municipalities.